2010
DOI: 10.1097/iae.0b013e3181d6def0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intravitreal Bevacizumab (Avastin) Injected at the End of Diabetic Vitrectomy in Preventing Postoperative Recurrent Vitreous Hemorrhage

Abstract: Intravitreal injection of 1.25 mg bevacizumab given at the end of vitrectomy appears safe and effective for reducing the incidence of recurrent postoperative vitreous hemorrhage after diabetic vitrectomy. Further randomized studies should be performed to evaluate the potential of this therapy in preventing postoperative recurrent vitreous hemorrhage after diabetic vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
3
30
0
1
Order By: Relevance
“…9,12 IVB after a vitrectomy also appears safe and effective for reducing postoperative VH, albeit without the benefit on final visual acuity. 21,22 In a randomized clinical trial, 25.7% of patients avoided the need for vitrectomy after IVB injection. 23 Although PRP is the principal therapy for PDR, substantial regression of NV may take weeks after completion of laser treatment, and it is not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 IVB after a vitrectomy also appears safe and effective for reducing postoperative VH, albeit without the benefit on final visual acuity. 21,22 In a randomized clinical trial, 25.7% of patients avoided the need for vitrectomy after IVB injection. 23 Although PRP is the principal therapy for PDR, substantial regression of NV may take weeks after completion of laser treatment, and it is not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to reduce intraoperative bleeding, provide a clear field for vascular epiretinal tissue dissection, and reduce the chance of recurrent hemorrhage [18,19,21,22]. Although tractional retinal detachment has been reported as a complication in these cases [20,22], secondary RRD as a complication of intravitreal bevacizumab has not been reported. This is despite the fact that neovascularization and fibrovascular proliferation is also seen in the natural course of proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 92%
“…Median age of the study population was 33 yrs (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The patients had presented with a median duration of vitreous hemorrhage of 5 months (3-7).…”
Section: Resultsmentioning
confidence: 99%
“…23 Some investigators have suggested the use of bevacizumab at the end of operation to reduce postoperative hemorrhage induced by early growth of neovascularization. 24,25 We injected 0.05 mg of bevasizumab before silicone oil infusion in an attempt to inhibit early postoperative neovascularization. The exact effect of the treatment in a silicone oil-filled eye remains to be studied.…”
Section: Discussionmentioning
confidence: 99%